(untitled) (Al-Academy, 2026)
This article examines the multifaceted nature of quality assurance in the garment industry, highlighting its critical role in meeting consumer expectations and ensuring product reliability within a competitive market. It addresses the challenges faced by both consumers and manufacturers when quality is compromised, illustrated through real-world examples of product defects. Emphasizing that quality is defined by customer perception rather than supplier claims, the study aligns with ISO 8402’s definition of quality. The research presents a comprehensive analysis of current quality assurance processes in garment manufacturing, identifying key factors influencing fabric quality, such as material selection, production techniques, and inspection methodologies. Advanced diagnostic tools, including statistical process control and root cause analysis, are employed to identify common defects and their origins in the production workflow. Additionally, a framework for continuous improvement is proposed, integrating methodologies like Total Quality Management (TQM) and Six Sigma to enhance quality assurance efforts. The implementation of automated inspection technologies and data-driven decision-making is discussed as a means to increase efficiency and reduce variability in fabric quality. By developing a comprehensive quality manual and automated tools for managing non-conformance, this study aims to provide valuable insights for enhancing operational efficiency and market competitiveness in the textile sector, fostering a culture of quality throughout the supply chain.